Students' perceptions on peer written feedback in narrative essays - Carvajal, Winma Jane P. (Journal of Action Research, 2014)
The study aimed to gain insights into the lack of consensus on the usefulness of peer feedback in improving student writing. It surveyed eighty (80) third year high school students of St. Scholastica's College, Manila. The survey questionnaire required respondents to grade their agreement or disagreement with each of the items that stated a particular perception on peer feedback. Ninety percent of the respondents agreed that peer-written feedback is useful in improving their drafts. The top three areas students perceived they improved on with help of peer feedback were motivation and encouragement, error correction, and organization and structure. Additionally, nearly all of the respondents agreed that the peer feedback process provides advantages to them as peer evaluators.